Left Maximum Minimum Cost Ideal Process -Secure and Unhinged Grid in Haze Computing - et. al., S. Janani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, proposed method namely Maximum Minimum LeftAllotment method is applied to seek the feasible solution with respect to Cost Optimization from the basic feasible solution set for transportation problems. The proposed algorithm is a different way to obtain the feasible (or) may be optimal (for some extant) solution without anxiety of degeneracy condition.